Bisnis dan Dakwah Dalam Tradisi Media (Kopi) di Provinsi Aceh - Mukhsinuddin, Mukhsinuddin; Hamsa, Amrizal; Bargie, Gamal (AT-TASYRI': JURNAL ILMIAH PRODI MUAMALAH, 2024)
The rapid growth of coffee shops in Aceh has established the region as a coffee production area. Among these establishments, some have embraced an Islamic concept in their business model by integrating religious content into their offerings, exemplified by the program "Ngopi juga Ngaji," which combines coffee enjoyment with religious learning. This research employs a qualitative ethnographic approach, conducted over 12 months in Banda Aceh. Data collection involved three stages: observation, interviews, and documentation. Once the data was gathered, it underwent processing that included verifying the information, coding, organizing, interpreting, and drawing conclusions. The findings reveal that several coffee shops in Aceh have introduced innovative practices by incorporating religious programs into their business model, reflecting Islamic principles. This approach emphasizes that business should not solely focus on profit but also serve as a platform for promoting religious teachings. The concept of dawah in coffee shops parallels the efforts of al-Banna to engage the community in Egypt, suggesting that such initiatives can positively impact the religious literacy of the younger generation. Therefore, coffee drinking can transcend mere socializing and become an avenue for spiritual growth and communal benefit.